From API to AI: platforms and their opacities. Issue 13 (10th November 2019) - Mackenzie, Adrian
ABSTRACT: Accounts of social network platforms have often stressed their programmability. The economic, social and technical fabric of social media has been directly associated with the code that modulates their connectivity and constructs opaque forms of property and capitalisation. The programmability of contemporary platforms is shifting in significant respects. By describing some recent shifts in programming practice at Facebook, the paper explores how predictive and machine learning approaches arise from a constitutive opacity present in all platform ensembles. It suggests that the growth in predictive programmability can be understood in terms of an increasingly experimental interplay between processes of platformisation and infrastructuralisation. Understanding these changes in programmability might be useful in analysing the relations between large information-communication ensembles and contemporary forms of life. It conceptualises, in particular, opacity as a constitutive problem for platforms rather than a proprietary limitation.